THE ROLE OF HEALTH PSYCHOLOGY IN THE FORMATION OF HEALTHY LIFESTYLE - Klicheva, Zulfiya Polatovna (SCIENCE and SOCIETY, 2026)
This article provides information on the role and importance of health psychology in shaping a healthy lifestyle, human psychological well-being, issues of maintaining and strengthening health, as well as the influence of psychological factors on a healthy lifestyle.
Keywords: Health psychology; healthy lifestyle; stress; socio-psychological factors; personality; behavior